Effectiveness of Problem Posing Model on Ability of High School Physics Teachers to Solve HOTS-Based Problems - Soewarno, Soewarno; Herliana, Fitria; Musdar, Musdar (Asian Journal of Science Education, 2020)
The importance of the teacher's role in mastering HOTS-based questions greatly influences the learning outcomes achieved by students. So we need an appropriate learning model to guide students to more easily solve HOTS-based problems. This study aims to determine the effectiveness of the Problem Posing model in improving the ability of high school physics teachers to solve HOTS-based problems. The method used in this study was quantitative research that was quasi-experimental with the design of One Group Pretest-Postest Design. This design consists of one group chosen randomly and it was given a pre-test before being given treatment. That group was given a treatment of applying the Problem Posing model and after that, the group was given a post-test to find out whether there was an effect of applying the Problem Posing model to the ability of physics teachers in solving HOTS-based problems. The study population included all physics teachers in Bener Meriah, Central Aceh. The research sample was taken using random sampling techniques. Data were collected from the results of the pretest and posttest done by the physics teacher, namely the Friction Force HOTS-Based Problems. The data is analyzed using two-tailed t-test formula. The results of data analysis obtained tcount ttable was 2.79 2.06 which means Ha is accepted and it was obtained an n-gain score of 64.69. Based on these results it could be concluded that the Problem Posing model is quite effectively used to improve the ability of teachers to solve HOTS-based problems.